Construction method of Ag-In-Ga-S quantum dot backlight film

By preparing the Ag-In-Ga-S quantum dot backlight film, the problems of high blue light transmittance and low fluorescence intensity of the backlight film in the prior art were solved, and the effect of improving the color reduction of the display was achieved, and new materials were provided for the field of backlight display.

CN119799313AActive Publication Date: 2025-04-11NANJING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411924102.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-11
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

In the prior art, the Ag-In-Ga-S quantum dot backlight film has a high blue light transmittance and low fluorescence intensity, resulting in a low color reduction degree of display and relatively lack of research.

Method used

Quantum dot powder was prepared by centrifugation, precipitation, dispersion and drying of the Ag-In-Ga-S quantum dot stock solution, and mixed with the polymer solution, and scraping and drying Ag-In-Ga-S quantum dot backlight film was prepared.

Benefits of technology

It has achieved the reduction of the blue light transmittance of the backlight film, improved its fluorescence intensity, improved the color reduction of the display, and provided new potential materials for the backlight display field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799313A_ABST
    Figure CN119799313A_ABST
Patent Text Reader

Abstract

The invention discloses a construction method of an Ag-In-Ga-S quantum dot backlight film, which comprises the following steps: taking an AIGS quantum dot stock solution, and carrying out post-treatment to prepare AIGS quantum dot powder; weighing a polymer, adding the polymer into a non-polar solvent, heating, stirring and dissolving to prepare a polymer solution; aIGS quantum dot powder and a polymer solution are stirred and mixed to be uniform, the mixture is poured on a flat plate, and a quantum dot initial thin film with the uniform thickness is formed through blade coating of a coating machine; and putting into a drying oven, and drying for a certain time at a certain temperature to obtain the AIGS quantum dot backlight film. The AIGS quantum dots are used as photoluminescent materials, and different types of AIGS quantum dot powder and a polymer solution are mixed and dried to prepare the AIGS quantum dot backlight film. According to the method, the fluorescence intensity of the AIGS quantum dot backlight film is improved, the blue light transmittance of the AIGS quantum dot backlight film is reduced, and the method is an ideal choice applied to the fields of next-generation illumination and high-definition display.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and in particular relates to a method for constructing an Ag-In-Ga-S quantum dot backlight film. Background Art

[0002] Traditional liquid crystal displays use cold cathode fluorescent lamps (CCFLS) as backlight sources. Due to their poor luminescence, the color of the light source is not accurate enough, resulting in low color reproduction. With the improvement of people's living standards, new requirements have been put forward for high-definition display of monitors. In recent years, quantum dots have replaced traditional phosphors due to their excellent luminescence properties (such as cadmium sulfide quantum dots). However, this type of quantum dots has disadvantages such as toxicity (cadmium element) and complex process, which limits its application in lighting and backlight display.

[0003] Cadmium-free and lead-free I-III-VI group quantum dots are a new type of environmentally friendly luminescent material. They have shown great potential in improving the luminous efficiency and color reproduction of displays due to their high photoluminescence quantum yield, high spectral tunability and stability, and have gradually become an important research direction in the field of luminescent displays. However, the current research on this type of quantum dots, especially Ag-In-Ga-S (AIGS) quantum dots, has just started, and the research on quantum dot backlight films is even more scarce. There are almost no reports on the problems of high blue light transmittance and low fluorescence intensity of backlight films.

[0004] Therefore, a method for constructing an Ag-In-Ga-S quantum dot backlight film is needed to solve the above problems. Summary of the invention

[0005] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for constructing an Ag-In-Ga-S quantum dot backlight film.

[0006] A method for constructing an Ag-In-Ga-S quantum dot backlight film comprises the following steps:

[0007] Step 1: Take the Ag-In-Ga-S quantum dot stock solution and centrifuge it;

[0008] Step 2: Take the supernatant obtained by centrifugation, add a precipitant thereto, mix well, and then centrifuge for a second time;

[0009] Step 3: dispersing the precipitate obtained by the second centrifugation in a dispersant, adding a precipitant thereto, mixing well, and centrifuging three times;

[0010] Step 4: Place the three centrifugal precipitates in an oven and dry them at a certain temperature for a period of time to obtain quantum dot powder;

[0011] Step 5: taking a certain amount of polymer and a non-polar solvent, mixing and heating, to obtain a polymer solution;

[0012] Step 6: taking a certain amount of the prepared quantum dot powder and mixing it with the polymer solution prepared in step 5 for a certain period of time to obtain a uniform and stable quantum dot polymer solution;

[0013] Step 7: pouring the quantum dot polymer solution obtained in step 6 onto a flat plate, and applying a coating by a coating machine to obtain an initial quantum dot film of uniform thickness;

[0014] Step 8: Place the initial quantum dot film in an oven and dry it at a certain temperature for a certain period of time to obtain an AIGS quantum dot backlight film.

[0015] Furthermore, the Ag-In-Ga-S quantum dot stock solution in step 1 is an AIGS quantum dot stock solution, an AIGS@GaS quantum dot stock solution or an AIGS@ZnS quantum dot stock solution.

[0016] Furthermore, the centrifugal speed in step 1, step 2 and step 3 is 6000 rpm to 11000 rpm, and the centrifugal time is 3 min to 8 min.

[0017] Furthermore, the precipitant in step 2 is polar solvent anhydrous ethanol, and the volume is 2 to 10 times that of the supernatant.

[0018] Furthermore, the dispersant in step 3 is toluene, n-hexane or n-octane, and the volume ratio of the dispersant to the Ag-In-Ga-S quantum dot stock solution is 0.5-2 mL: 2-5 mL; the precipitant is a polar solvent anhydrous ethanol, and the volume is 2-10 times that of the dispersant.

[0019] Furthermore, in step 4, the drying temperature of the quantum dot precipitate is 20°C to 80°C, and the drying time is 2h to 8h. In step 8, the drying temperature is 20°C to 100°C, and the drying time is 2min to 12h.

[0020] Furthermore, the polymer in step 5 is methyl methacrylate PMMA, polyvinyl alcohol PS or polyethylene oxide PEO, and the mass volume ratio of the polymer to the Ag-In-Ga-S quantum dot stock solution is 0.25g~1.25g:2~5mL.

[0021] Furthermore, the non-polar solvent in step 5 is n-hexane, n-octane or toluene, and the volume ratio of the non-polar solvent to the Ag-In-Ga-S quantum dot stock solution is 2-5 mL: 2-5 mL.

[0022] Furthermore, in step 6, the mass volume ratio of the quantum dot powder to the Ag-In-Ga-S quantum dot stock solution is 0.02-0.08 g: 2-5 mL, and the mixing time is 10-30 min.

[0023] Furthermore, the coating thickness in step 7 is 100 μm to 1200 μm.

[0024] Principle of the invention: Different from the traditional method of mixing cadmium-based and lead-based quantum dots with polymers to prepare backlight films, the present invention uses cadmium-free and lead-free AIGS quantum dots to mix with polymer solutions and stir evenly, and obtains a uniform and stable AIGS quantum dot backlight film through processes such as scraping and drying.

[0025] Beneficial effects: The method for constructing the Ag-In-Ga-S quantum dot backlight film of the present invention is simple to operate, has a high repetition rate, is conducive to industrial mass production, and provides a new potential material for the backlight display field. The construction of the AIGS quantum dot backlight film is realized, and an AIGS quantum dot backlight film is prepared by mixing the AIGS quantum dot powder with a non-polar solution of a polymer, and then coating and drying the mixture; the blue light transmittance is reduced by changing the amount of quantum dot powder added, and the fluorescence intensity of the backlight film is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The X-ray diffraction patterns of Example 1 and Comparative Example 3 of the present invention;

[0027] Figure 2 is a comparison chart of transmittance between Example 1 of the present invention and Comparative Examples 1, 2, and 3;

[0028] Figure 3 is a transmittance comparison diagram of Examples 1, 2, and 3 of the present invention and Comparative Example 3;

[0029] Figure 4 The emission spectra of Example 1 of the present invention and Comparative Examples 1 and 2 are compared;

[0030] Figure 5 This is a comparison diagram of the emission spectra of Example 1 and Examples 2 and 3 of the present invention;

[0031] Figure 6 This is a picture of LED under blue light (450nm) excitation in Example 1 of the present invention;

[0032] Figure 7 This is a picture of LED under blue light (450nm) excitation in Example 2 of the present invention;

[0033] Figure 8 This is a picture of LED under blue light (450nm) excitation in Example 3 of the present invention;

[0034] Fig. 9It is a comparison diagram of emission spectra of Examples 1 and 4 of the present invention. DETAILED DESCRIPTION

[0035] The preferred embodiments of the present invention will be described below in conjunction with the accompanying drawings to more clearly and completely illustrate the technical solutions of the present invention.

[0036] Example 1

[0037] The method for constructing the Ag-In-Ga-S quantum dot backlight film of the present invention comprises the following steps:

[0038] Step 1: Take 5 mL of AIGS@GaS quantum dot stock solution, centrifuge at 8000 rpm for 5 min, obtain 2 mL of the upper clear liquid, add 10 mL of anhydrous ethanol, centrifuge twice at 8000 rpm for 5 min, obtain the lower precipitate, take 2 mL of toluene to disperse it, add 10 mL of anhydrous ethanol and mix evenly, centrifuge three times at 8000 rpm for 5 min, take the lower precipitate, and send it into an oven to dry at 60°C for 2 h to obtain powdered quantum dots.

[0039] Step 2: Mix 1 g of PMMA with 4 mL of toluene at 90°C and heat until dissolved, then cool.

[0040] Step 3: Add 0.08 g of AIGS@GaS quantum dot powder into the toluene solution of PMMA and stir evenly.

[0041] Step 4: Pour the AIGS@GaS quantum dots and PMMA toluene solution prepared in step 3 onto a glass plate and apply a scraper with a thickness of 1000 μm, then place the glass plate in an oven for drying to obtain an AIGS@GaS quantum dot backlight film.

[0042] Example 2

[0043] The same process as in Example 1 was adopted except that the 0.08 g powder quantum dots in step 3 were replaced with 0.02 g, and other conditions remained the same.

[0044] Example 3

[0045] The same process as in Example 1 was adopted except that the 0.08 g powder quantum dots in step 3 were replaced with 0.04 g, and other conditions remained the same.

[0046] Example 4

[0047] The same process as in Example 1 is adopted except that the AIGS@GaS quantum dot stock solution in step 1 is replaced with AIGS quantum dot stock solution, and other conditions remain the same.

[0048] Comparative Example 1

[0049] The same process as in Example 1 is adopted, except that the quantum dot precipitate obtained by centrifuging the AIGS@GaS quantum dot stock solution in step 1 is sent to an oven for drying, and the obtained powder is mixed with the toluene solution of PMMA.

[0050] Comparative Example 2

[0051] The same process as in Example 1 is adopted, except that the quantum dot precipitate obtained by secondary centrifugation of the AIGS@GaS quantum dot stock solution in step 1 is sent to an oven for drying, and the obtained powder is mixed with the toluene solution of PMMA.

[0052] Comparative Example 3

[0053] The same process as in Comparative Example 1 was adopted except that powdered quantum dots were not added, and other conditions remained the same.

[0054] Depend on Figure 1 It can be seen that drying the quantum dots and adding them to the toluene solution of PMMA does not affect the original crystal structure of the quantum dots, and the main diffraction peaks of the obtained quantum dots are all within the range of the diffraction peaks of AgInS2 and AgGaS2, indicating that the synthesized product is Ag-In-Ga-S quaternary quantum dots.

[0055] Depend on Figure 2 It can be seen that the blue light transmittance of the quantum dot backlight film made of quantum dot powder that has been centrifuged three times is reduced from 30% after only one centrifugation to 21%.

[0056] Depend on Figure 3 It can be seen that the blue light (450nm) transmittance of the quantum dots in the quantum dot backlight film made of quantum dot powder with increased quantum dot content is reduced from 85% to 21%.

[0057] Depend on Figure 4 It can be seen that under the same excitation light (480nm) and the same slit, the fluorescence intensity of the quantum dot backlight film made from powder quantum dots that have been centrifuged three times is the highest.

[0058] Depend on Figure 5 It can be seen that under the same excitation light (480 nm) and the same slit, the fluorescence intensity of the quantum dot color conversion film prepared with an addition amount of 0.08 g of powder quantum dots is the highest.

[0059] Depend on Figure 6 It can be seen that in Example 1, after the AIGS quantum dot backlight film with 0.08 g of quantum dots added was excited by the blue light chip, it achieved 545 nm peak luminescence, and the blue light luminescence peak was relatively low.

[0060] Depend on Figure 7It can be seen that after adding 0.04g of quantum dots to the AIGS quantum dot backlight film of Example 3, it achieved 545nm peak luminescence after being excited by the blue light chip, and the blue light peak was relatively high.

[0061] Depend on Figure 8 It can be seen that in Example 2, after the AIGS quantum dot backlight film with 0.02 g of quantum dots added was excited by the blue light chip, a weak 545 nm peak luminescence was achieved, and the blue light peak was relatively high.

[0062] Depend on Fig. 9 It can be seen that after adding different types of AIGS quantum dots in Examples 1 and 4, the backlight films achieved different peak luminescence. The luminescence peaks of AIGS@GaS and AIGS quantum dot backlight films were 545nm and 630nm, respectively, showing relatively standard green and red fluorescence, laying the foundation for realizing lighting and display applications.

[0063] In summary, the present invention provides a method for constructing an Ag-In-Ga-S quantum dot backlight film, which reduces the blue light transmittance of the backlight film while increasing the fluorescence intensity of the backlight film by adjusting parameters such as the number of post-processing times, drying time, drying temperature, and quantum dot types.

Claims

1. A method for constructing an Ag-In-Ga-S quantum dot backlight film, characterized in that it comprises the following steps: Step 1: Take the Ag-In-Ga-S quantum dot stock solution and centrifuge it; Step 2: Take the supernatant obtained by centrifugation, add a precipitant thereto, mix well, and then centrifuge for a second time; Step 3: dispersing the precipitate obtained by the second centrifugation in a dispersant, adding a precipitant thereto, mixing well, and centrifuging three times; Step 4: Place the three centrifugal precipitates in an oven and dry them at a certain temperature for a period of time to obtain quantum dot powder; Step 5: taking a certain amount of polymer and a non-polar solvent, mixing and heating, to obtain a polymer solution; Step 6: taking a certain amount of the prepared quantum dot powder and mixing it with the polymer solution prepared in step 5 for a certain period of time to obtain a uniform and stable quantum dot polymer solution; Step 7: pouring the quantum dot polymer solution obtained in step 6 onto a flat plate, and applying a coating by a coating machine to obtain an initial quantum dot film of uniform thickness; Step 8: Place the initial quantum dot film in an oven and dry it at a certain temperature for a certain period of time to obtain an AIGS quantum dot backlight film.

2. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The Ag-In-Ga-S quantum dot stock solution in step 1 is an AIGS quantum dot stock solution, an AIGS@GaS quantum dot stock solution or an AIGS@ZnS quantum dot stock solution.

3. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The centrifugal speed in step 1, step 2 and step 3 is 6000 rpm~11000 rpm, and the centrifugal time is 3 min~8 min.

4. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The precipitant in step 2 is polar solvent anhydrous ethanol, and the volume is 2 to 10 times that of the supernatant.

5. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The dispersant in step 3 is toluene, n-hexane or n-octane, and the volume ratio of the dispersant to the Ag-In-Ga-S quantum dot stock solution is 0.5~2mL:2~5mL; the precipitant is polar solvent anhydrous ethanol, and the volume is 2~10 times that of the dispersant.

6. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: In step 4, the drying temperature of the quantum dot precipitation is 20°C~80°C, and the drying time is 2h~8h. In step 8, the drying temperature is 20°C~100°C, and the drying time is 2min~12h.

7. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The polymer in step 5 is methyl methacrylate PMMA, polyvinyl alcohol PS or polyethylene oxide PEO, and the mass volume ratio of the polymer to the Ag-In-Ga-S quantum dot stock solution is 0.25g~1.25g:2~5mL.

8. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The non-polar solvent in step 5 is n-hexane, n-octane or toluene, and the volume ratio of the non-polar solvent to the Ag-In-Ga-S quantum dot stock solution is 2~5mL:2~5mL.

9. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The mass volume ratio of the quantum dot powder and the Ag-In-Ga-S quantum dot stock solution in step 6 is 0.02-0.08 g: 2-5 mL, and the mixing time is 10-30 min.

10. The method for constructing the Ag-In-Ga-S quantum dot backlight film according to claim 1, characterized in that: The coating thickness in step 7 is 100 μm to 1200 μm.

Citation Information

Patent Citations

  • Film comprising bright silver-based quaternary nanostructures

    CN116981754A

  • Stabilized AIGS membranes

    CN117396581A

  • Method for improving fluorescence quantum yield of Ag-In-Ga-S quaternary quantum dots

    CN117402612A

  • Films comprising bright silver based quaternary nanostructures

    US20230002672A1

  • Quantum dots, quantum dot composition, and electronic device using same

    WO2024205018A1